A Synthesis of Systemic Action Research Processes in the CLARISSA Programme on Worst Forms of Child Labour - Burns, Danny; Apgar, Marina (Institute of Development Studies, 2024)
This paper describes, synthesises and analyses the work of 25 Action Research Groups that were the heartbeat of the CLARISSA Systemic Action Research programme. The CLARISSA programme worked to create participatory and systemic solutions to the worst forms of child labour in the adult entertainment sector in Nepal, and the leather sector in Bangladesh. The paper explores how the action research groups were set up, and how they worked through key stages of trust and relationship building, generating evidence, building theories of change, planning and taking action, and assessing the effects of that action. The paper, which is a synthesis of the evidence and learning produced in the programme, draws together learning about the process for both ground-level action researchers and those who might fund, design or implement future programmes.

Reframing, refining, and reconceptualising the worst forms of child labour through participatory adaptive programming - Apgar, Marina; Burns, Danny (Journal of modern slavery, 2021)
This article explores the potential of using participatory action research as an adaptive programming modality to drive learning and innovation to tackle the drivers of (and seek to eliminate) the Worst Forms of Child Labour. We draw on our experience from early phases of implementation of a large-scale action research programme, which despite the constraints covid-19 posed in moving to full implementation and participatory engagement with children and other stakeholders on the ground, is already generating rich learning about the opportunities and challenges of designing programmes that respond to the complex reality of WFCL. We share early learning about what it takes to be fully open to using the lived experience of programme development, and early findings from scoping and mapping of the dynamics of social norms, business practices and urban neighbourhoods and supply chains influencing WFCL in Bangladesh and Nepal, to frame and reframe the questions and response strategies and operationalise a participatory adaptive intent to work with hidden and complex dynamics that characterise the WFCL.

Learning from Life Story Collection and Analysis With Children Who Work in the Worst Forms of Child Labour in Nepal - Karki, Shanta; Apgar, Marina; Snijder, Mieke; Sharma, Ranjana (Institute of Development Studies, 2022)
The CLARISSA Nepal team collected and analysed 400 life stories of children and young people engaged in or affected by the worst forms of child labour (WFCL), particularly in the “Adult Entertainment” sector in Nepal, which includes children working in Dohoris (restaurants playing folk music), dance bars, spa-massage parlours, khaja ghars (tea/snack shop) and guest houses. Stories were also collected from children in CLARISSA’s focus neighbourhoods, children in this category include street connected children and those working in transportation, party palaces, domestic labour and construction sites. Of the 400 stories collected, 350 were collected by adult researchers and 50 were collected by children themselves.
Accepted: 2022-11-04T12:22:13Z

Bridging Learning and Action: How Did CLARISSA’s Participatory Adaptive Management Approach Foster Innovation, Effectiveness, and Stakeholder Empowerment? - Prieto Martin, Pedro; Apgar, Marina; Afroze, Jiniya; Arulanantham, Amit; Hicks, Jacqueline; Karki, Shanta; Mareschal, Sophie; Paul, Sukanta; Snijder, Mieke; Uddin, Forhad; Veitch, Helen (Institute of Development Studies, 2024)
Child Labour: Action-Research-Innovation in South and South-Eastern Asia (CLARISSA) is an evidence and innovation-generation programme funded by the United Kingdom’s Foreign, Commonwealth & Development Office (FCDO), responding to the challenge of the worst forms of child labour (WFCL) in Bangladesh and Nepal. It is a challenge characterised by a poor understanding of its drivers and a lack of evidence on what works to combat it. To handle such fundamental uncertainty, the programme adopts a child-centric and participatory action research approach, which is supported by an adaptive management model to respond better to challenges and opportunities. From its inception, the programme needed to navigate shocks and challenges, such as Covid-19 lockdowns, political upheaval, and sustained budget cuts, which put its capacity to learn and evolve to the test. This paper shares insights emerging from evaluating CLARISSA’s participatory adaptive management (PAM) practices, connecting them with current discussions on adaptive management. It provides an in-depth evaluation of CLARISSA’s PAM approach, exploring how adaptive strategies were implemented and evolved throughout the programme’s life cycle. Multiple cases of adaptation and misadaptation were selected and analysed through a series of in-depth interviews and review of programme documentation, allowing us to assess whether and how the adaptive management practices have been operationalised, the degree to which they led to enhanced decision-making and effectiveness, and their empowering effect on children and other programme stakeholders. Through conceptual analysis and real-world examples, the paper examines the key stages and critical dimensions of PAM, conveying the complexities and dynamism of adaptive management in development work, while highlighting both the successes and challenges encountered in operationalising PAM within CLARISSA.
Accepted: 2024-05-10T08:21:46Z